Emotions, stress, anxiety and coping: a qualitative study with international level coaches - Dias, Cláudia; Cruz, José Fernando; Fonseca, António Manuel (Brazilian journal of physical education and sport, 2010)
The influence of psychological factors on athletes' sport performance is, in general, well documented; however, there is little understanding of the role these factors and processes play in coaches. In this sense, using a semi-structured interview, the present study aimed to identify, in six elite coaches aged between 55 and 63 (M = 59 ± 3.03) and representing diverse sports, the most important psychological skills and characteristics for obtaining success, the major sources of stress and anxiety and the coping strategies most used in problematic and stressful situations; additionally, the role of further emotions, other than anxiety, in competitive performance, was also explored. The results revealed that: 1) motivation was considered one of the most important psychological skills/ characteristics for success in sport; 2) the major sources of stress were related with athletes' performance; 3) the coaches used several coping strategies simultaneously, usually adaptative; 4) in addition to anxiety, other positive and negative emotions influenced coaches' performance.